(untitled) (Research, Society and Development, 2023)
This article investigates the role of psychologists, guided by psychoanalytic theory, in providing assistance to children who are victims of violence and access the SUAS (Unified System for Social Assistance) in Brazil. In this regard, it seeks to identify the legal guidelines regulating the psychologist’s role in the SUAS and in cases of child violence; examine the employed interventions and how they impact the individuals involved; and analyze the main challenges faced by psychologists in this context. The research adopted an exploratory qualitative methodology, using semi-structured interviews with open-ended questions to collect data. The Child and Adolescent Statute emerges as the primary legal framework guiding the work within the SUAS for children who are victims of violence. The psychologist’s role is psychosocial, involving psychosocial actions both individually and in groups, considering social phenomena and the subjectivity of the individuals. In working with children, play is used to facilitate free association, a psychoanalytic method that allows unconscious contents to emerge in discourse and be elaborated. This way, children may break the cycle of violence and discover new possibilities for their existence in the world. Challenges described by interviewees include the difficulty of listening to children’s narratives without becoming emotionally affected to the point where it hinders their effectiveness, limited resources for their work, the complexities of interdisciplinary collaboration, and integrating psychoanalytic principles into the realm of social assistance. It is emphasized that further research is needed to disseminate knowledge about this practice and improve the approaches used.